Impact of Wind Generation Fluctuations in the Design and Operation of Power Systems - Estanqueiro, Ana (2010)
In this paper, the impact of the wind time variability and the spatial smoothing effect in mountainous complex terrains, usually taken as 1/sqrt(N) for fast fluctuations, is studied. The dimension of the regions, the type of electrical clustering of large numbers of wind turbines and the local meteorological effects are addressed and conclusions drawn on selected experimental case studies.